Comparative analysis of methods to minimize dust from granite mine dumps - Tverda, Oksana; Tkachuk, Kostyantyn; Davydenko, Yuliia (Eastern-European Journal of Enterprise Technologies, 2016)
The measures to reduce the concentration of dust from the mine dump are selected. The criteria for their evaluation and factors of significance are identified to compare them and determine the method that will allow gaining the most ecological and economic effect of its implementation. The solution to this problem is possible using the method of the "best alternative in multicriteria problems". The advantage of this method is accounting of assessment criteria of dust reduction methods and their factors of significance. The research allows determining the most appropriate method to minimize dust from the mine dumps by the main criteria: economic costs, the specific consumption of the substance used, the possibility of dust collection in the air, dust emission reduction level, the maximum distance from the dump, the emergence of new harmful compounds, the possibility of use in different seasons. It is proved that the dust reduction method, which corresponds to the application of the polymer solution, and is 0.95 has the highest rate of the membership function among others.